Prototype Development for Solar Energy Tracking Based on Arduino in QUEST Campus Larkana - Abdul Hameed soomro; SanaUllah Talani; Talha Soomro; Faraz Ali Khushk; Ahmer Ali Bhatti (Sir Syed University Research Journal of Engineering and Technology)
The utilization of solar energy has become increasingly popular due to its renewable and sustainable nature. However, one of the primary challenges in solar energy harvesting is the optimization of the amount of energy that can be captured from the sun. The implementation of solar trackers is an effective solution that enables the automatic adjustment of the solar panel's position to face the sun throughout the day. In this project, an Arduino-based solar tracker prototype was designed and implemented to optimize the solar energy harvesting process. The system employs Light-Dependent Resistors (LDRs) to detect sunlight intensity and a servo motor to adjust the position of the solar panel accordingly. The system was programmed using the Arduino programming language and was tested using a small-scale solar panel. The increasing demand for cost-effective and easy-to-install renewable energy systems has led to a growing interest in photovoltaic solar energy for residential use. To optimize energy production, a two-axis photovoltaic solar tracker that orients the solar panel toward the maximum solar radiation is proposed in this study. The use of Free Computer Aided Design (CAD) 0.15 for the prototype's design, combined with Arduino technology, provides an affordable solution for mounting the solar tracker on flat roofs and other horizontal building elements. The performance of the solar tracker was evaluated under various testing conditions, showcasing an enhanced level of accuracy and energy production when compared to traditional fixed systems. The prototype's successful demonstration represents a significant advancement in the field, providing a practical solution for small-scale and residential solar energy applications. This research prototype was developed and installed on the roof of the Electrical department of QUEST, Campus Larkana, and validated through simulation results.